Faktor Penerapan Metode Penggunaan Teknologi Beton Precast pada Kontruksi di Kota Surabaya - Pratama, Arfi Wahyu; Tjendani, Hanie Teki; Firmansyah, Mochamad (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
Construction projects are characterized by high complexity and constraints in time, cost, and resources, requiring efficient construction methods. One of the emerging methods is precast concrete. This study aims to identify the factors influencing the implementation of precast methods in construction projects in Surabaya. A quantitative approach was used, with data collected through questionnaires distributed to 50 respondents consisting of contractors and project management personnel. Data analysis was conducted using Partial Least Square (PLS). The results indicate that all indicators have outer loading values > 0.7, AVE > 0.5, and Composite Reliability > 0.7, confirming that the constructs are valid and reliable. The main factors influencing precast implementation include technical, managerial, and human resource aspects, with coordination among project stakeholders identified as the most dominant factor. The findings of this study are expected to support decision-making in selecting more effective construction methods.